2007
DOI: 10.1038/sj.emboj.7601967
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic histone H3 methylation during gene induction: HYPB/Setd2 mediates all H3K36 trimethylation

Abstract: Understanding the function of histone modifications across inducible genes in mammalian cells requires quantitative, comparative analysis of their fate during gene activation and identification of enzymes responsible. We produced high-resolution comparative maps of the distribution and dynamics of H3K4me3, H3K36me3, H3K79me2 and H3K9ac across c-fos and c-jun upon gene induction in murine fibroblasts. In unstimulated cells, continuous turnover of H3K9 acetylation occurs on all K4-trimethylated histone H3 tails;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
430
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(477 citation statements)
references
References 71 publications
32
430
3
1
Order By: Relevance
“…Mammalian H3K36 methyltransferases include SMYD2, 46 NSD1 47 and the Set2 homolog HYPB/ SETD2. 48 H3K36 methyltransferase activity has also been suggested for ASH1. 49 NSD1 is of particular interest as it is involved in a leukemogenic translocation that depends on enzymatic activity of the methyltransferase domain.…”
Section: H3k36 Methylationmentioning
confidence: 99%
“…Mammalian H3K36 methyltransferases include SMYD2, 46 NSD1 47 and the Set2 homolog HYPB/ SETD2. 48 H3K36 methyltransferase activity has also been suggested for ASH1. 49 NSD1 is of particular interest as it is involved in a leukemogenic translocation that depends on enzymatic activity of the methyltransferase domain.…”
Section: H3k36 Methylationmentioning
confidence: 99%
“…S2), suggesting a more prominent role for NSD1 in establishing the trimethylated histone lysines residues. To reinforce the concept that NSD1 was the enzyme mainly responsible for the described histone trimethylated marks in our tumoral context, we analyzed the expression levels of other histone methyltransferases targeting these particular lysines, such as SET2 (HYPB/HIF-1, KMT3A) and SMYD2 (KMT3C), which specifically methylate H3-K36 (20,21), and Pr-SET7/8 (KMT5A) and SUV4-20h1,h2 (KMT5B,C), which have been implicated in the monomethylation and trimethylation of H4-K20 (22,23). We observed similar expression of these four enzymes in cancer cells with hypermethylated and unmethylated NSD1 (Fig.…”
Section: Nsd1 Epigenetic Silencing In Cancer Cells Is Associated Withmentioning
confidence: 99%
“…Among them, the authors identified mono-methylation on K525 residue (K525me1) of STAT1 to be critical for IFN-α-induced STAT1 interaction with JAK1 kinase and for phosphorylation, nuclear translocation, and DNA-binding activity of STAT1. Since SETD2 is a known histone methyltransferase that catalyzes the methylation of H3K36 [7,8], the authors further examined whether SETD2 is responsible for K525 methylation of STAT1. Indeed, SETD2-F2 overexpression enhanced the monomethylation of STAT1, whereas silencing of SETD2 reduced the K525me1 of STAT1 induced by IFN-α stimulation.…”
mentioning
confidence: 99%